2016
DOI: 10.1111/oik.03707
|View full text |Cite
|
Sign up to set email alerts
|

Neutral or non‐neutral communities: temporal dynamics provide the answer

Abstract: Neutral models for community dynamics are based on the assumption that temporal variation is only influenced by demographic stochasticity, ignoring the influence of fluctuations in the environment. Demographic and environmental stochasticity are known to have very different effects on the population dynamics of single species. Communities, however, are usually analyzed with emphasis on the shape of the species abundance distribution rather than on their dynamical characteristics. Accordingly, examination of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 92 publications
0
15
0
1
Order By: Relevance
“…Thus, we approximate the density in the noise term by the equilibrium density, Q i , and study relative deviations from this density, z i ðxÞ ¼ n i ðxÞ=Q i À 1. It has previously been shown that approximate results based on a small noise assumption and linearization in models similar to this one are remarkably accurate under moderate and even fairly large population density fluctuations (Engen et al 2017). The linearized version of Eq.…”
Section: Model and Methodsmentioning
confidence: 93%
“…Thus, we approximate the density in the noise term by the equilibrium density, Q i , and study relative deviations from this density, z i ðxÞ ¼ n i ðxÞ=Q i À 1. It has previously been shown that approximate results based on a small noise assumption and linearization in models similar to this one are remarkably accurate under moderate and even fairly large population density fluctuations (Engen et al 2017). The linearized version of Eq.…”
Section: Model and Methodsmentioning
confidence: 93%
“…Of the few studies that do consider finer-scale outcomes such as abundances over time, most examine the effects of demographic stochasticity alongside other factors such as dispersal (Alexander et al 2012), priority effects (Mertz et al 1976, Fukami 2004 or density manipulations (Svensson et al 2018). These approaches are incomplete because even with fine experimental control, the effects of demographic stochasticity are difficult to isolate from other drivers of variability without ample time-series data (Vellend et al 2014, Engen et al 2017, and the application of detailed stochastic population models (Melbourne and Hastings 2008).…”
Section: Introductionmentioning
confidence: 99%
“…We show that when b(x), d(x) and c(x) have a particular functional form (see Eq. (12)(13)(14)) the invariant distribution is a beta distribution (Eq. (15)).…”
Section: The Modelmentioning
confidence: 99%
“…The recent development of neutral approaches to the study of ecological systems [7][8][9][10] have provided a renewed emphasis upon the value of theory and stochasticity in ecology [11][12][13][14] and a locus for the further integration of genetical and ecological theories 15,16 . By merging the mathematical and statistical tools developed by population geneticists with the neutrality approach, neutral theory in ecology allows us to better understand the factors affecting the abundance and distribution of species [15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%